2021
DOI: 10.3390/rs13245117
|View full text |Cite
|
Sign up to set email alerts
|

Glacier Area and Snow Cover Changes in the Range System Surrounding Tarim from 2000 to 2020 Using Google Earth Engine

Abstract: Glacier and snow are sensitive indicators of regional climate variability. In the early 21st century, glaciers in the West Kunlun and Pamir regions showed stable or even slightly positive mass budgets, and this is anomalous in a worldwide context of glacier recession. We studied the evolution of snow cover to understand whether it could explain the evolution of glacier area. In this study, we used the thresholding of the NDSI (Normalized Difference Snow Index) retrieved with MODIS data to extract annual glacie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 94 publications
1
5
0
Order By: Relevance
“…In terms of sub-region scale, it was found that glaciers in the Eastern Tianshan and Dzhungarsky Alatau have most significant negative mass balance rate (Barandun et al, 2021). In contrast, the annual mass balance variability was lower in the Central Tianshan (Barandun et al, 2021), and the glacier area shrinkage rate in the Northern/Western Tianshan had spatial variability ranging from 0.11%/a to 3.7%/a (Zhang et al, 2021), which was more consistent with our results. Huang et al (2021) suggested that the glacier area shrinkage rate in the Eastern Tianshan was 0.8%/a between 1990 and 2018, but our results show that the glacier loss rate in the Eastern Tianshan consistently exceeded 2%/a.…”
Section: Comparison With Other Regions Across the Tianshansupporting
confidence: 89%
“…In terms of sub-region scale, it was found that glaciers in the Eastern Tianshan and Dzhungarsky Alatau have most significant negative mass balance rate (Barandun et al, 2021). In contrast, the annual mass balance variability was lower in the Central Tianshan (Barandun et al, 2021), and the glacier area shrinkage rate in the Northern/Western Tianshan had spatial variability ranging from 0.11%/a to 3.7%/a (Zhang et al, 2021), which was more consistent with our results. Huang et al (2021) suggested that the glacier area shrinkage rate in the Eastern Tianshan was 0.8%/a between 1990 and 2018, but our results show that the glacier loss rate in the Eastern Tianshan consistently exceeded 2%/a.…”
Section: Comparison With Other Regions Across the Tianshansupporting
confidence: 89%
“…The overlapping data at each pixel position formed a pixel set. Usually, the minimum or median of pixel sets is used to synthesize images [40,41,52]. The image synthesis process is shown in Figure 3, followed by image collection, cloud filtering, and image synthesis.…”
Section: Image Synthesismentioning
confidence: 99%
“…The band ratio method [8], NDSI method [6], and RF method [9,10] are commonly used in glacier extraction. In this study, the three methods were used for the widely used median composite image and minimum composite image [40,41,52]. There were six methods in total: the band ratio method based on median composite image (Median_Band) (B4/B6 > 5.0), the band ratio method based on minimum composite image (B4/B6 > 5.0), the NDSI method based on median composite image (Median_NDSI) (NDSI > 0.4, NDWI < 0.3), the NDSI method based on minimum composite image (Min_NDSI) (NDSI > 0.4, NDWI < 0.6), the RF method based on median composite image (Median_RF), and the RF method based on minimum composite image (Min_RF).…”
Section: Comparison and Analysis With Glacier Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…Baba et al 14 combined MERRA-2 and ERA5 satellite data to analyze the spatial distribution of snow water equivalent in the High Atlas region, and the results show that the snow water equivalent distribution obtained from the combination of the two satellites performs well in the snowpack area during most of the hydrological year. Zhang et al 15 extracted glacier and snow cover areas from MODIS data and studied the relationship between glacier evolution trends and snow cover evolution in the Tarim Basin.…”
Section: Introductionmentioning
confidence: 99%